Trends and recent progresses of selenium nanoparticles as novel autophagy regulators for therapeutic development - Chen, Dongsheng; Lu, Hongmei; Ma, Yuhe; Huang, Yuhe; Zhang, Tangxin; Fan, Shuhao; Lin, Wensen; Huang, Yifan; Jin, Hua; Ruan, Yongdui; Xu, Jun-Fa; Pi, Jiang (Frontiers in Nutrition, 2023)
Autophagy, one of the major intracellular degradation systems, plays an important role in maintaining normal cellular physiological functions and protecting organisms from different diseases. Selenium (Se), an essential trace element, is involved in many metabolic regulatory signaling events and plays a key role in human health. In recent years, selenium nanoparticles (Se NPs) have attracted increasing attentions in biomedical field due to their low toxicity, high bioavailability and high bioactivity. Taking the advantage of their advanced biological activities, Se NPs can be used alone as potential therapeutic agents, or combine with other agents and served as carriers for the development of novel therapeutics. More interestingly, Se NPs have been widely reported to affect autophagy signaling, which therefor allow Se NPs to be used as potential therapeutic agents against different diseases. Here, this review suggested the relationships between Se and autophagy, followed by the trends and recent progresses of Se NPs for autophagy regulation in different diseased conditions. More importantly, this work discussed the roles and potential mechanisms of Se NPs in autophagy regulating, which might enhance our understanding about how Se NPs regulate autophagy for potential disease treatment. This work is expected to promote the potential application of Se NPs as novel autophagy regulators, which might benefit the development of novel autophagy associated therapeutics.